Antimycobacterial activity of the plectasin derivative NZ2114 - Davids, Camilla; Rao-Fransson, Komal; Krishnan, Nitya; Tenland, Erik; Mörgelin, Matthias; Robertson, Brian; Godaly, Gabriela (Frontiers in Microbiology, 2025)
IntroductionMycobacteria have a unique hydrophobic membrane with several lipid-enriched layers that are low in permeability, setting them apart from other bacteria. This complex structure, consisting of three distinct layers is crucial for cell growth, virulence, and providing a barrier to antibiotics. Previously, we identified a plectasin variant, NZX, which showed activity against Mycobacterium tuberculosis in several murine tuberculosis (TB) infection studies. In this study, we investigated another plectasin variant, NZ2114, known for its effectiveness against Gram-positive bacteria, as a potential antimycobacterial peptide both in vitro and in vivo.MethodsThe resazurin microtiter assay (REMA) was used to determine MIC; a time-kill assay was performed to evaluate long-term effects; scanning electron microscopy (SEM) was employed to visualize peptide impact; a checkerboard assay assessed drug compatibility; MTT and WST-8 assays were used to estimate peptide toxicity; intracellular killing was evaluated using primary macrophages; peptide stability was assessed in human serum; and a murine tuberculosis (TB) infection model was used to verify the peptide’s efficacy.ResultsNZ2114 effectively killed mycobacteria at a minimal inhibitory concentration (MIC99) of 6.1 µM, was non-toxic to primary human cells, and remained resistant to serum degradation while preserving its antimycobacterial capacity. In a checkerboard assay, NZ2114 demonstrated synergy with the first-line TB drugs isoniazid and ethambutol. The antimicrobial effect was also observed against several clinical isolates of Gram-positive bacteria, including Enterococcus faecalis, Enterococcus faecium, and Methicillin-Resistant Staphylococcus aureus (MRSA). In our murine TB infection model, compared to untreated controls, NZ2114 eliminated M. tuberculosis with a log reduction of 0.72 (81.14%) after three doses.DiscussionThese studies suggest NZ2114 as a potential TB therapy, aiding in the control of this significant infectious disease.